Overview of FBO Licensing in the India and New Dietary Ingredient Notification in the US - B, Nandhini; Venkatesh, MP; Kumar, TM Pramod (Indian Journal of Pharmaceutical Education and Research, 2021)
The nutraceuticals in India are termed as "Foods for Special Dietary Uses" Food Safety and Standards Authority describes "Nutraceuticals provide a physiological benefit and help to maintain good health." FSSAI was recognized in India under the 2006 Food Safety and Standards Act, combines several acts and guidelines that existed in various ministries and departments to deal with food related substances. In US regulation, dietary supplements define “dietary supplement in part as product taken by mouth that contain a dietary ingredient. Dietary ingredients include nutrients, minerals and vitamins amino acids and herbs or botanicals and many other ingredients that can be used to enhance the diet. Demand for nutraceuticals is growing day by day, it has been noted that around 60-70% of dietary supplements marketed in India are false, counterfeit, unsecured and unauthorized. It is a problem that has not gone unnoticed by both the regulator and the industry. To take advantage of this demand, many new companies have begun manufacturing nutraceuticals. FSSAI has defined regulatory guidelines for approval of nutraceuticals in the Indian market. The aim of this article to have a closer look at nutraceuticals and their Food Business Operator (FBO) licensing, registration procedure and FSSAI key criteria for manufacturing nutraceuticals in India compared to US dietary supplement, submission and approval of NDI notification for New Dietary Ingredient. The nutraceutical industry has now developed into a growing organization fuelled by intense efforts to identify nutraceutical product characteristics and prospective applications, combined with customer demand and requirements.
Keywords: FSSAI; Nutraceuticals; Dietary Supplements; Food Business Operator; DSHEA